Sociodemographic Characteristics of Women Able to Obtain Medication Abortion Before and After Ohio's Law Requiring Use of the Food and Drug Administration Protocol - Upadhyay, Ushma D. (Health Equity, 2018)
Purpose: In 2011, a law went into effect in Ohio that regulates how abortion care providers can offer medication abortion to their patients. We sought to evaluate changes in sociodemographic characteristics of Ohio medication abortion patients before and after the implementation of this law. Methods: We used a retrospective cohort design, comparing characteristics of women obtaining a medication abortion at four abortion facilities before and after the law. We used chart data from January 2010 to January 2011 and February 2011 to October 2014. For any significant changes in sociodemographics found before and after the law, we used stratified cross-tabulations to disentangle whether they were likely related to the restricted gestational limit imposed by the law (lowered from 9 to 7 weeks gestation), or whether they were likely related to other burdens brought on by the law, such as increased costs and visits. Results: Women obtaining a medication abortion after the law were more likely to be older (p=0.01), have higher levels of education (p<0.001), be of white race (p<0.001), have private insurance (p=0.001), have no children (p=0.002), and reside in a higher income zip code (p=0.03). Both the reduced gestational limit and the increased costs and visits likely contributed to declines among black women and women with lower levels of education. The reduced gestational limit for medication abortion likely contributed to a decline among younger women and Medicaid recipient groups. The increased costs and visits imposed by the law likely contributed to the decline in medication abortion among women with no insurance and women with children. Conclusion: The lower gestational limit, higher cost, and time and travel burdens exacted by Ohio's medication abortion law were associated with disproportionate reductions in medication abortion among the most disadvantaged groups. The law was associated with reduced access among women who were younger, of black race, less educated, and in lower socioeconomic groups.